Gravity Casting Of Variable Composition Al Alloys: Innovation And New Potentialities. (2019) - Lombardo, Silvia; Peter, Ildiko; Rosso, Mario
Abstract: Aluminum alloys are the most employed light alloys in the automotive sector. Therefore, aluminum-alloy production process must be flexible and competitive in order to meet the market needs. This study analyzes an innovative production process for aluminum alloys that can be employed for engine components like pistons. This kind of engine parts are typically subjected in service to high temperatures and fatigue stresses. The aim of this work is to define a sequential casting process for the production of a Functionally Graded Material (FGM) component with high-temperature resistance and ductility. The employ of two distinct aluminum alloys is at issue